The relevance of biologically effective dose for pain relief and sensory dysfunction after Gamma Knife radiosurgery for trigeminal neuralgia: an 871-patient multicenter study - Warnick, Ronald E; Paddick, Ian; Mathieu, David; Adam, Elizabeth; Iorio-Morin, Christian; Leduc, William; Hamel, Andréanne; Johnson, Sarah E; Bydon, Mohamad; Niranjan, Ajay; Lunsford, L Dade; Wei, Zhishuo; et al. (Journal of neurosurgery, 2024)
OBJECTIVE: Recent studies have suggested that biologically effective dose (BED) is an important correlate of pain relief and sensory dysfunction after Gamma Knife radiosurgery (GKRS) for trigeminal neuralgia (TN). The goal of this study was to determine if BED is superior to prescription dose in predicting outcomes in TN patients undergoing GKRS as a first procedure. METHODS: This was a retrospective study of 871 patients with type 1 TN from 13 GKRS centers. Patient demographics, pain characteristics, treatment parameters, and outcomes were reviewed. BED was compared with prescription dose and other dosimetric factors for their predictive value. RESULTS: The median age of the patients was 68 years, and 60% were female. Nearly 70% of patients experienced pain in the V2 and/or V3 dermatomes, predominantly on the right side (60%). Most patients had modified BNI Pain Intensity Scale grade IV or V pain (89.2%) and were taking 1 or 2 pain medications (74.1%). The median prescription dose was 80 Gy (range 62.5-95 Gy). The proximal trigeminal nerve was targeted in 77.9% of cases, and the median follow-up was 21 months (range 6-156 months). Initial pain relief (modified BNI Pain Intensity Scale grades I-IIIa) was noted in 81.8% of evaluable patients at a median of 30 days. Of 709 patients who achieved initial pain relief, 42.3% experienced at least one pain recurrence after GKRS at a median of 44 months, with 49.0% of these patients undergoing a second procedure. New-onset facial numbness occurred in 25.3% of patients after a median of 8 months. Age ≥ 63 years was associated with a higher probability of both initial pain relief and maintaining pain relief. A distal target location was associated with a higher probability of initial and long-term pain relief, but also a higher incidence of sensory dysfunction. BED ≥ 2100 Gy2.47 was predictive of pain relief at 30 days and 1 year for the distal target, whereas physical dose ≥ 85 Gy was significant for the proximal target, but the restricted range of BED values in this subgroup could be a confounding factor. A maximum brainstem point dose ≥ 29.5 Gy was associated with a higher probability of bothersome facial numbness. CONCLUSIONS: BED and physical dose were both predictive of pain relief and could be used as treatment planning goals for distal and proximal targets, respectively, while considering maximum brainstem point dose < 29.5 Gy as a potential constraint for bothersome numbness.
Keywords: výsledek terapie; Male; retrospektivní studie; Trigeminal Neuralgia; následné studie; měření bolesti; Adult; Aged; dospělí; mužské pohlaví; senioři; radiochirurgie; Follow-Up Studies; Treatment Outcome; senioři nad 80 let; lidé; ženské pohlaví; Humans; Aged, 80 and over; Radiosurgery; neuralgie trigeminu; Retrospective Studies; Female; Pain Measurement; lidé středního věku; Middle Aged